Short-term effects of bokashi fertilizer with reduced NPK fertilization on soil fertility, growth, and yield of rubber trees - Gashua, Auwalu Garba; Sulaiman, Zulkefly; Mohammad Yusoff, Martini; Abd. Samad, Mohd Yusoff; Ramlan, Mohd Fauzi; Mokhatar, Shafar Jefri (Universiti Putra Malaysia, 2023)
Rubber is currently the second major industrial crop in Malaysia after oil palm. The use of bokashi fertilizer (BF) on industrial crops is still not popular, and farmers rely mostly on chemical fertilizers (CFs) that are costly and hazardous to the environment. This research was conducted at Hevea plantation, Universiti Putra Malaysia, between August 2020–October 2021. The study was to assess the short-term effects of BF with reduced NPK fertilization on soil fertility, growth, and yield of rubber. Seven treatments (T) were involved. T1, T2, and T3 denote 4, 8, and 12 kg BF per pit. T4 was 1 kg NPK as control, whereas T5, T6, and T7 denote 4, 8, and 12 kg BF + 500 g NPK per pit, respectively. The variables observed included total nitrogen (TN%), total phosphorus (TP%), organic carbon (OC%), organic matter (OM%), exchangeable cations, microbial counts, tree girth, and dry rubber yield. The major findings indicated that applying 12 kg BF has raised the soil’s TN%, OC%, and OM% by 165, 171.4, and 172.0%, respectively, compared to NPK control. Also, adding 4 kg BF + 500 g NPK has increased the soil’s cation exchange capacity and TP% values by 107.8 and 42.9%, respectively, compared to the control. Adding sole bokashi increased the bacterial population by 22.2–133.3%. Rubber yield was better on trees treated with 12 kg BF, though this did not differ significantly from other treatments. Therefore, applying 12 kg BF or 4 kg BF + 500 g NPK can improve soil fertility and save costs from using inorganic fertilizer by at least 50%.